آراء بنت الشاطئ في بعض مباحث علوم القرآن : " دراسة تحليلية من خلال كتابها " التفسير البياني - Arhami Abdullah Akhili
This research is a study of a highly distinguished exegesis, Al-Tafsir al-Bayani li al-Qur'an al-Karim by Professor 'A'ishah bint ʿAbd al-Raḥman, better known as Bint al-shaṭiʾ, which aims to elaborate on the characteristics and the methodology of Qur’an interpretation that she applied in her exegesis. This study attempts to discuss issues related to aspects of the Sciences of the Quran within her exegesis, by emphasizing on the several remarkable points comprising of some of her new thoughts and opinions that contradict the majority of exegetes. Hence, this study focuses on these thoughts by analysing in detail how she navigates the topic of Sciences of the Quran. This discussion will involve six topics, which are: Scientific interpretation (Al-Tafsir al-ʿIlmi), Reasons of Revelation (Asbab al-Nuzul), Repetition in the Qur’an (Al-Tikrar), Rhymed verses in the Qur’an (Fawaṣil al-Ayat), Abbreviated Letters (Al-Huruf al-Muqaṭṭaʿah), and Oaths in the Qur’an (Al-Qasm). This study is guided by two main methods, which are the phenomenological method (an in-depth study of Bint Shati’e’s exegesis), and the analytical method (a discussion and analysis of Bint Shati’e’s opinions and that of other scholars) by extracting the related discussion from primary and secondary sources, including other prominent and notable exegeses as well as other references of the Sciences of the Quran for comparison. The findings reveal her most significant thoughts and opinions on the six selected topics, as well as the parallel and dissenting opinions of other renowned exegetes.